Valuation and investment profession - Lidija Dedi; Philippe Giraudon (UTMS Journal of Economics, 2013)
Investment professionals, particularly financial analysts or security analysts evaluate securities and try to determine characteristics of securities and to identify mispriced securities. For that purpose they use different models to estimate the intrinsic value of the common stocks. Traditional valuation models based on the present value of future cash flows are affected by estimated growth rate of the variable used and by the investor's required rate of return. These models can be used for valuing fixed income securities, such as bonds and preferred stocks. However, in valuing companies with significant growth opportunities they have to expand traditional analysis with option valuation.
Keywords: G12; G13; 330; investment professions; valuation; dividend discount models; free cash flow model; option value